Assessment of groundwater contamination risk and seasonal dynamics of microelement composition in groundwater: A case study from the Karadag State Nature Reserve, Crimean Peninsula - Pham, Cam Nhung; Lapchenko, Vladimir; Lapchenko, Elena; Tabunshchik, Vladimir (Brawijaya University, 2025)
The chemical composition of the water was determined to obtain a general picture of the geographical distribution of elements and identify the peculiarities of the elemental and chemical composition of groundwater. The analysis of heavy metal concentrations in the four wells, situated within the territory of the Karadag Reserve, revealed seasonal variations. An increase in macroelement concentrations was observed during winter, while their levels decreased during summer. The concentrations of microelements such as B (boron) and Fe (iron) decreased with increasing distance from the sea during winter and increased during summer. The analysis also identified significant exceedances of the maximum permissible concentrations (MPC) for heavy metals Li, B, Mg, Ca, Fe, Ni, and Br, as well as occasional exceedances of sodium and manganese concentrations. For all elements, the contamination factor (CF) was calculated. Based on the CF values, the pollution load index (PLI) was calculated to assess the degree of pollution by the studied elements. The results indicate the absence of pollution in the investigated area, both in summer and winter periods. To determine the degree of anthropogenic pollution by elements, the geoaccumulation index (Igeo) was calculated. Most of the studied elements do not indicate pollution either in summer or winter. However, the Igeo values for calcium indicate a moderate level of pollution during summer and a higher level during winter. The overall analysis of the results suggests that there is no serious groundwater pollution issue in the studied area by the analyzed elements.